INSAN education: Towards responsible internet users - Surbakti, Feliks Prasepta Sejahtera (Universitas Muhammadiyah Magelang, 2025)
The use of the internet has become an integral part of modern life. However, various threats, such as the dissemination of personal data, phishing attacks, hoaxes, and illegal content, pose risks to user security. Therefore, it is crucial to educate the public about the principles of Safe and Healthy Internet Usage (INSAN). This initiative aims to raise awareness and understanding within the community regarding the importance of responsible internet use and compliance with applicable regulations. The initiative employs interactive presentations and simulations of best practices in internet use. Educational activities engage various stakeholders, including students, teachers, and the general public, to foster a comprehensive understanding of cybersecurity. Results indicate increased participant awareness of internet threats like hoaxes and phishing, and the adoption of preventive measures, such as installing antivirus software, verifying news sources, and limiting the sharing of personal information online. In conclusion, this initiative successfully enhanced digital literacy within the community and provided practical guidance for creating a safer digital environment.